The The Socio-natural operations in slide-show Oaks? of Stefan Wojnecki - Łuczak, Dorota (Porównania, 2022)
The subject of this text is the audiovisual project Oaks? by Stefan Wojnecki, which was created with the collaboration of Maria Ewa Wiesner and Jerzy Dorn in 1974 and has so far been absent from the art-historical literature and from the history of Polish photography. This work is presented as an example of ecological art that not only manifests the need to protect the environment, but encourages an empathetic reevaluation of socio-environmental relations. In the experience of being ill and undergoing life-saving surgery represented in Oaks?, the author of the article notes ideas anticipating the posthumanist abolition of hierarchical human domination in favor of equal relations of human and non-human entities.